The 60 nm gold nanoparticles improve qPCR amplification efficiency through specific palindromic sequences (GGATCC or ACCGGT) in primers - Zeng, Ruyu; Du, Zhiqun; Ma, Hongliang; Meng, Xiuqiong; Li, Erhua; Li, Jiangchao (Biochimica et biophysica acta. General subjects, 2024)
Polymerase chain reaction (PCR) technology and quantitative real-time PCR (qPCR) technology are widely used in clinical diagnosis and research, but amplification efficiency and sensitivity are still key problems for researchers. An increasing number of reports show that gold nanoparticles (AuNPs) can be used to improve the sensitivity and amplification efficiency of PCR. Here, we found that 60 nm gold nanoparticles with a positive charge (60 nm- Au+) can enhance the amplification efficiency of qPCR. Mouse DNA was extracted by the alkaline lysis method. Primer 5.0 software was used to design primers and mutation primers, and the DNA fragments were obtained by the method of synthesizing plasmids. The qPCR was applied to amplify target gene fragments. The amplification efficiency of qPCR was improved by about 1.828 times in the experimental group with 60 nm- Au+ compared with the control group without 60 nm- Au+. The primer pair contains a specific palindromic sequence (GGATCC or ACCGGT). And 60 nm Au+ did not enhance the amplification efficiency of qPCR when the above primer was mutated. The primers contain special palindrome sequences (GGATCC or ACCGGT) with 60 nm- Au+ can enhance the amplification efficiency of qPCR. Therefore, it suggests a more in-depth understanding of the mechanism and function of gold nanoparticles and primer sequences. This study has presented some implications for gold nanoparticles application in the development of qPCR technology. •Now, it is controversial whether AuNPs promote PCR amplification efficiency.•60 nm- Au+ promotes the amplification efficiency of qPCR with primers containing palindromic sequences.•Mutating palindromic sequences in primers did not again improve the amplification efficiency of qPCR.•It suggested the AuNPs and some special DNA primers are associated with the qPCR amplification system.